Downregulation of keratin 76 expression during oral carcinogenesis of human, hamster and mouse. - Srikant Ambatipudi; Priyanka G Bhosale; Emma Heath; Manishkumar Pandey; Gaurav Kumar; Shubhada Kane; Asawari Patil; Girish B Maru; Rajiv S Desai; Fiona M Watt; Manoj B Mahimkar (PLoS ONE, 2013)
Keratins are structural marker proteins with tissue specific expression; however, recent reports indicate their involvement in cancer progression. Previous study from our lab revealed deregulation of many genes related to structural molecular integrity including KRT76. Here we evaluate the role of KRT76 downregulation in oral precancer and cancer development.We evaluated KRT76 expression by qRT-PCR in normal and tumor tissues of the oral cavity. We also analyzed K76 expression by immunohistochemistry in normal, oral precancerous lesion (OPL), oral squamous cell carcinoma (OSCC) and in hamster model of oral carcinogenesis. Further, functional implication of KRT76 loss was confirmed using KRT76-knockout (KO) mice.We observed a strong association of reduced K76 expression with increased risk of OPL and OSCC development. The buccal epithelium of DMBA treated hamsters showed a similar trend. Oral cavity of KRT76-KO mice showed preneoplastic changes in the gingivobuccal epithelium while no pathological changes were observed in KRT76 negative tissues such as tongue.The present study demonstrates loss of KRT76 in oral carcinogenesis. The KRT76-KO mice data underlines the potential of KRT76 being an early event although this loss is not sufficient to drive the development of oral cancers. Thus, future studies to investigate the contributing role of KRT76 in light of other tumor driving events are warranted.